Implementation Of Islamic Education Values In The Islamic Boarding School Tradition Of Leran Manyar Gresik Village - Fafi ‘Alimah Rosyidah; Muhamad Arif (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
In carrying out the cultural mandate, humans cannot be separated from the elements of life which also include global cultural establishment factors, such as technological systems, work patterns, language, social institutions, educational methods, arts, and beliefs. One of the main sources of national wealth is cultural diversity in the form of the richness and charm of the archipelago whose beauty cannot be denied. In local traditions, there are many messages and meanings implicit in the cultural diversity spread throughout the archipelago. So improving education in the village of Leran Manyar Gresik must be considered for the development of local traditions in the advancement of human civilization. The focus of this research includes: 1) How are the values of Islamic education implemented in the Islamic boarding school tradition in the Islamic boarding school hamlet of Leran Manyar Gresik village? 2) What are the values of Islamic education in the Islamic boarding school tradition found in the Islamic boarding school hamlet of Leran Manyar Gresik village? This research uses a qualitative method with an ethnographic approach, which aims to describe and develop the way of life (why of life) of society's culture and social structure. Based on the results of this research, show that the implementation of Islamic education values in the Islamic boarding school tradition of Leran Manyar Gresik village is by instilling, understanding, and getting used to the values of Islamic education in the form of the obligation to pray in congregation, the obligation to cover one's private parts, the prohibition on women going out without the assistance of a mahram, the prohibition on committing immoral acts. starting from early childhood to adulthood by evaluating Islamic boarding school traditions with the entire community of Leran Manyar Gresik village at the end of each month, to determine the development and decline of Islamic boarding school traditions.